Operational performance improvement through continuous improvement initiatives in micro-enterprises of Turkey - Gurkan Inan, Guven; Gungor, Zahit Ergun; Bititci, Umit Sezer; Abdul Halim-Lim, Sarina (Emerald Publishing, 2021)
Purpose – Micro-enterprises have a vital role in the development of a nation by creating employment, encouraging entrepreneurship, balancing social income and educating the workforce. Yet, micro-enterprises face significant operational challenges such as low productivity, high production costs and long changeover times. These challenges are often overlooked by researchers and practitioners but have a drastic impact on micro-enterprises’ operational performance. With over 95% of the economy consisting of micro-enterprises, it is vital to improve operational performance and competitiveness of the micro-enterprises. Design/methodology/approach – Considering the data availability and practical challenges of gathering data from micro-enterprises, an action research methodology was selected as a suitable research method. Following the initial diagnostic visits, planned interventions were prepared and results were observed to gather data and draw conclusions. Findings – Findings suggest that commonly adapted performance improvement initiatives by large enterprises cannot be directly applied in micro-enterprises to enhance operational performance. Microenterprises lack the critical resources and company culture to easily adapt these initiatives. On the other hand, when these performance improvement initiatives are filtered according to specific needs of micro-enterprises, continuous improvement initiatives were often found to be effective in improving operational performance. Specifically, 5S, single-minute exchange of dies (SMED), suggestion schemes, layout improvements, management coaching, visual management, empowerment were found to be useful and suitable to address command and control culture, low productivity, unorganised workspace, undelegated authority, low skilled employees and unwillingness to take responsibility problems. Research limitations/implications – Further research is required to investigate the specific factors that affect the adaptation of continuous improvement initiatives such as culture and industry type. Originality/value – This research extends and contributes the current literature on continuous improvement initiatives by revealing how performance improvement initiatives need to be filtered according to the specific needs of micro-enterprises, and how these initiatives can be used to address specific problems to improve operational efficiency. It provides a conceptual framework to guide the decision-making process on operational performance improvement in micro-enterprises.